In-vitro biological screening of methanol extract of aporosa wallichii (euphorbiaceae) leaves - Islam, Md. Nasiful (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017.